2015
DOI: 10.1175/mwr-d-15-0065.1
|View full text |Cite
|
Sign up to set email alerts
|

Precipitation Properties Observed during Tropical Cyclone Intensity Change

Abstract: Using a 15-yr (1998–2012) multiplatform dataset of passive microwave satellite data [tropical cyclone–passive microwave (TC-PMW)] for Atlantic and east Pacific storms, this study examines the relative importance of various precipitation properties, specifically convective intensity, symmetry, and area, to the spectrum of intensity changes observed in tropical cyclones. Analyses are presented not only spatially in shear-relative quadrants around the center, but also every 6 h during a 42-h period encompassing 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
74
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(90 citation statements)
references
References 42 publications
16
74
0
Order By: Relevance
“…This is consistent with Alvey III et al (2015). They examined the precipitation properties of TCs as a function of the intensity changes based on 15 years of passive microwave satellite data, and indicated that the rate of symmetrization in precipitation distribution increased with increasing rate of intensity change.…”
Section: Significance Testssupporting
confidence: 68%
“…This is consistent with Alvey III et al (2015). They examined the precipitation properties of TCs as a function of the intensity changes based on 15 years of passive microwave satellite data, and indicated that the rate of symmetrization in precipitation distribution increased with increasing rate of intensity change.…”
Section: Significance Testssupporting
confidence: 68%
“…In fact, Alvey et al (2015) and Klotz and Jiang (2017) presented a new method for calculating full storm symmetry. In this study, we define "symmetry index" as the ratio of minimum to maximum quadrant size.…”
Section: Symmetry Indexmentioning
confidence: 99%
“…Alvey et al (2015) showed that RI events have more symmetric distributions of precipitation prior to onset of intensification, as well as a greater overall areal coverage of precipitation. We used AMSU measurements from six satellites: AQUA, MetOp, NOAA-15, NOAA-16, NOAA-17, and NOAA-18.…”
mentioning
confidence: 98%